Black Rot of Orchids Caused by Phytophthora palmivora and Phytophthora cactorum - Robert A. Cating; Aaron J. Palmateer; Carol M. Stiles; P. A. Rayside; D. A. Davison (EDIS, 2009)
PP260, a 5-page illustrated fact sheet by R. A. Cating, A. J. Palmateer, C. M. Stiles, P. A. Rayside, and D. A. Davison, describes this disease of orchids, its host range, symptoms, diagnosis, management, and nursery sanitation recommendations. Includes references. Published by the UF Department of Plant Pathology, January 2009.